School Admissions Reform in Chicago and England: Comparing Mechanisms by their Vulnerability to Manipulation - Pathak, Parag A; Sönmez, Tayfun (American Economic Review, 2013)
In Fall 2009, Chicago authorities abandoned a school assignment mechanism midstream, citing concerns about its vulnerability to manipulation. Nonetheless, they asked thousands of applicants to re-rank schools in a new mechanism that is also manipulable. This paper introduces a method to compare mechanisms by their vulnerability to manipulation. Our methodology formalizes how the old mechanism is at least as manipulable as any other plausible mechanism, including the new one. A number of similar transitions took place in England after the widely popular Boston mechanism was ruled illegal in 2007. Our approach provides support for these and other recent policy changes. (JEL C78, D82, H75, I21, I28)